CHILDREN’S DIETARY HABITS AND EARLY CHILDHOOD TOOTH DECAY (International journal of medical sciences, 2025)
Early childhood tooth decay is one of the most common dental health problems affecting children worldwide. This study examines the relationship between children’s dietary habits and the development of tooth decay in early childhood. Frequent sugar consumption, sticky foods, nighttime sweetened drinks, irregular meal schedules, and insufficient intake of minerals and vitamins were identified as major risk factors. Family feeding practices and parental guidance were found to significantly influence children’s eating behaviors and oral health outcomes. Preventive measures such as structured meal times, limiting sugary foods, promoting water intake, mineral-rich diets, regular oral hygiene, and routine dental visits were shown to effectively reduce decay risk. The findings emphasize the importance of scientifically informed dietary regulation and parental involvement as key strategies for maintaining oral health and preventing early childhood tooth decay.